2010
DOI: 10.1128/jvi.01990-09
|View full text |Cite
|
Sign up to set email alerts
|

Residues in the Heptad Repeat A Region of the Fusion Protein Modulate the Virulence of Sendai Virus in Mice

Abstract: While the molecular basis of fusion (F) protein refolding during membrane fusion has been studied extensively in vitro, little is known about the biological significance of membrane fusion activity in parainfluenza virus replication and pathogenesis in vivo. Two recombinant Sendai viruses, F-L179V and F-K180Q, were generated that contain F protein mutations in the heptad repeat A region of the ectodomain, a region of the protein known to regulate F protein activation. In vitro, the F-L179V virus caused increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 76 publications
0
13
0
1
Order By: Relevance
“…A study published in 2010 showed that mutation of a single amino acid in Sendai virus F, which created a hyperfusogenic mutant, was also linked to enhanced pulmonary inflammation in vivo (21). A more recent report on parainfluenza virus 5 described a mechanism by which a single amino acid mutation in F causing greater fusion activity also resulted in differential recognition of the virus by the complement pathway (45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study published in 2010 showed that mutation of a single amino acid in Sendai virus F, which created a hyperfusogenic mutant, was also linked to enhanced pulmonary inflammation in vivo (21). A more recent report on parainfluenza virus 5 described a mechanism by which a single amino acid mutation in F causing greater fusion activity also resulted in differential recognition of the virus by the complement pathway (45).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have defined domains and specific residues important for fusion activity of RSV F (15)(16)(17)(18)(19)(20); however, the impact of fusion activity on paramyxovirus pathogenesis is not well understood. A pair of reports on Sendai virus demonstrated residues in heptad repeat A of F that enhance or dampen fusion activity and modulate pathogenesis (21,22). A hyperfusogenic mutation in Sendai virus F resulted in greater pathogenesis and mortality than the wild-type virus in the DBA/2 mouse model used, while a hypofusogenic mutation resulted in lessened mortality and pathogenesis compared to those of the wild-type virus (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the indicated days, nasal, tracheal, and lung tissues were excised, homogenized, and resuspended in 1 ml PBS containing Ca 2ϩ and Mg 2ϩ . Virus loads were determined by plaque titration in LLC-MK2 cells as described previously (34). Prior to imaging, mice were injected intraperitoneally (i.p.)…”
Section: Viruses and Cellsmentioning
confidence: 99%
“…However, circulating virus is faced with the challenge of withholding transition until an appropriate host cell membrane is available. Correlation has been found between an increase in fusion activity and higher viral load and pathogenesis in mice for both RSV (33) and other paramyxoviruses (34). Thus, circulating virus faces competing selective pressures of balancing the infectious half-life of transmitted virions and fusion capacity.…”
Section: Discussionmentioning
confidence: 99%